2008
DOI: 10.1161/circresaha.108.177105
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ, a Th1 Cytokine, Regulates Fat Inflammation

Abstract: Abstract-Adipose tissue (AT) can accumulate macrophages and secrete several inflammatory mediators. Despite its pivotal role in the progression of chronic inflammatory processes such as atherosclerosis, the adaptive role of immunity in obesity remains poorly explored. Visceral AT of diet-induced obese C57BL/6 mice had higher numbers of both CD4 ϩ and CD8 ϩ T cells than lean controls, monitored by flow cytometry. When stimulated in vitro, T cells from obese AT produced more interferon (IFN)␥ than those from con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
403
5
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(443 citation statements)
references
References 35 publications
27
403
5
8
Order By: Relevance
“…In fact, ceramide has been shown to be synthesized by long-chain fatty acids and to induce both inflammation and insulin resistance. 23 In agreement with our results, Rocha et al 5 reported that the HFD feeding increases a number of T cells and IFN-␥ gene expression in adipose tissue, suggesting T-cell priming toward the T H 1 slant. However, the HFD feeding has been shown to suppress T H 1 responses in B6 mice by inhibiting toll-like receptor-mediated maturation and proinflammatory cytokine production in dendritic cells.…”
Section: Ohmura Et Al Natural Killer T Cells and Glucose Intolerancesupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, ceramide has been shown to be synthesized by long-chain fatty acids and to induce both inflammation and insulin resistance. 23 In agreement with our results, Rocha et al 5 reported that the HFD feeding increases a number of T cells and IFN-␥ gene expression in adipose tissue, suggesting T-cell priming toward the T H 1 slant. However, the HFD feeding has been shown to suppress T H 1 responses in B6 mice by inhibiting toll-like receptor-mediated maturation and proinflammatory cytokine production in dendritic cells.…”
Section: Ohmura Et Al Natural Killer T Cells and Glucose Intolerancesupporting
confidence: 92%
“…However, the abolished monocyte and macrophage recruitment into peripheral tissue via interaction with MCP-1 could not completely inhibit HFD-mediated metabolic disorders, suggesting that other inflammatory cells may play a role in this context. Wu et al 4 and Rocha et al 5 demonstrated that CD3-positive T lymphocytes are present in human adipose tissue; and regulated upon activation, normal T cell expressed secreted (RANTES), a T-cell-specific chemokine, and its respective receptor CCR5 are expressed in adipose tissue from obese patients. However, the role of other types of lymphocytes in adipose tissue inflammation is largely unexplored.…”
mentioning
confidence: 99%
“…With regards to the cellular source contributing to the increased IL-10 production in the Il10-KO BMT mice, the BMT technique not only largely repopulates the recipient's monocytes/macrophages with those of the donor, but also the resident liver Kupffer cells [8,18], which are likely potential sources of liver-derived IL-10 production [29]. In addition, the BMT repopulates other bone-marrow-derived leucocytes, including lymphocytes, which are potent IL-10 producers and have also been shown to infiltrate adipose tissue and are implicated in adipose tissue inflammation and insulin resistance [39][40][41][42][43][44][45][46][47]. It is worth noting that, similarly to the global Il10-KO mice that develop chronic enterocolitis [21,22], a proportion (7/18) of our Il10-KO BMT mice developed mild colitis-like symptoms including loss of total body weight, loss of LBM, a failure to put on total body and fat mass with a high-fat diet, loose stools and a generally dehydrated and poor appearance.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant to our studies because we found that the expression of mRNA of markers of T(h)1 and CD8 + cells was reduced in adipose tissue of ob/obErk1 −/− mice. As a consequence, Ifng expression was also reduced, and this could have contributed to a reduction in fat inflammation [34,35]. Another possible explanation could be an impairment in the production of inflammatory cytokines by M1 macrophage that lack ERK1.…”
Section: Discussionmentioning
confidence: 99%